A new high‐resolution melt curve eDNA assay to monitor the simultaneous presence of invasive brown trout (Salmo trutta) and endangered galaxiids. Issue 3 (24th October 2020) - Minett, Jessica F.; Garcia de Leaniz, Carlos; Brickle, Paul; Consuegra, Sofia
Abstract: Brown trout are highly invasive in the Southern Hemisphere where they support important sport fisheries and aquaculture activities, which may impact endangered native galaxiid fishes and cause conflicts. To protect native galaxiids it is essential to monitor changes in species distributions, but this can be difficult when species are rare or difficult to sample. We developed and validated, both in the laboratory and in the field, a new assay using a high‐resolution melt curve (HRM)‐eDNA approach to simultaneously detect the presence of two threatened native galaxiids ( Aplochiton zebra and Aplochiton taeniatus ) and the invasive brown trout ( Salmo trutta ). Using this method, we found brown trout in 30% of the sampled waterbodies and Aplochiton sp. in 15% of them. Galaxiids were solely identified as being present in rivers that lacked brown trout, with both native species coexisting in two of the three rivers where they were detected, despite their different niche preferences. These assays can be used to monitor threatened zebra trout as well as invasive brown trout populations, allowing conservation managers to target areas for intervention. Abstract : We have developed two novel eDNA‐based assays for detecting invasive brown trout and two galaxiid species in the Falkland Islands, where brown trout was introduced about 100 years ago for angling purposes and represents one of the main threats for these protected species.